Antidiabetic, antioxidant activities and bioactive compound profile of extracts and fractions of tawar seribu root (Bauhinia purpurea) - Rizka Mulya Miranti; Yulianita Pratiwi Indah Lestari; Nurul Fajeriyati (JURNAL ILMU KEFARMASIAN INDONESIA, 2026)
Diabetes mellitus is a global health challenge that requires innovative solutions. This study aimed to evaluate the antidiabetic and antioxidant potentials of the root extract and its fractions of Bauhinia purpurea (Tawar Seribu). Extraction was performed using 95% ethanol as a solvent through the maceration method, followed by stepwise fractionation with n-hexane, ethyl acetate, and water. The biological activities were evaluated using the α-glucosidase enzyme inhibition assay for antidiabetic activity and the DPPH assay for antioxidant activity. The results revealed that The aqueous fraction exhibited the strongest α-glucosidase inhibitory activity (IC50 = 26.61 ppm), whereas the ethyl acetate fraction exhibited the highest antioxidant activity (IC50 = 36.73 ppm). GC-MS analysis revealed the presence of bioactive compounds such as 24-norursa-3,12-diene, olean-12-en-3-ol acetate, and lupeol, which support these biological activities. This study concludes that tawar seribu root holds great potential as a natural alternative for managing diabetes and oxidative stress, paving the way for further development as an effective and safe herbal medicine.